Bestimmung des Zersetzungsgrades von biologisch abbaubaren Kunststoffmaterialien unter nachgebildeten Heimkompostierungsbedingungen in Anlehnung an ISO 20200:2015 als Feldversuch - Marianne Münster (2022)
Today, plastic can be found in almost all areas of everyday life. Its properties - long durability, moldability, low weight, low manufacturing costs - provide unlimited applications. However, the disadvantages of plastics are becoming increasingly apparent: eventually the products become waste. This leads to enormous damage in climate and environment no matter how advanced a waste management is. Plastics are largely synthesized from organic materials such as petroleum, cellulose and coal. This results in resource consumption of raw materials and land. Furthermore, the monocultures cause a loss of biodiversity. A huge quantity of the plastic produced ends up in the environment. The decomposition process is very slow. Over time, the plastic parts decompose into smaller and smaller fragments. These are ingested by organisms and hence enter the ecosystems. Meanwhile, plastic particles can be found almost everywhere: in rivers, lakes, oceans and in the soil. In addition, it already has been found in many foods and in drinking water. To give plastics the desired attributes, many chemicals are used, such as antioxidants, plasticizers, flame retardants, biocides, and UV and heat stabilizers. They often also contain residues of the starting and auxiliary materials from the manufacturing process. For plasticizers alone, a large number of harmful effects on aquatic organisms have been proven. This being the case, alternative products appear desirable. These products should not pose a permanent impact on humans and the environment. For the production fewer resources should be consumed. The market for so-called "bioplastics" is growing steadily. Bioplastics consist of different materials with different qualities. It is considered a bioplastic if it is either biobased or biodegradable or both. This paper examines the status of bioplastics and their use, focusing on biodegradable plastics. Critical points and oppositions to their production, application and use are listed. Options of different disposal methods are presented and the limitations of the current technical standards of several countries in Europe are explained. The biodegradable plastics can disturb the composting process or reduce the compost quality. These materials are thermally recycled. The EU project Bio-Plastics Europe also deals with sustainable strategies and solutions for biobased and biodegradable plastics. Products are being created whose material properties should be qualitatively comparable to those of conventional plastics. The raw materials come from renewable sources that do not compete with the food supply. The aim of this thesis is to determine the degree of decomposition of materials from the EU project. These materials are PLA, PBS and PHBV. At present there is only limited data on the biodegradation of bioplastics in garden compost. For the labeling of a biodegradable plastic standardized requirements has been developed. The time period within which a biodegradable plastic decomposes and the degree of decomposition depend on several parameters. Plastics labeled as biodegradable often only degrade under specific conditions that are not met in a natural environment. Therefore, the degradability in home compost is investigated. For this purpose, a test method is being developed which is based on near-natural conditions. EN ISO 20200:2015 is used as the scientific basis. Over an 8-week composting period in a rotatable drum composter, the composting process and the test materials are observed and documented. After this period, an analysis of the test material is carried out using Differential Scanning Calorimetry (DSC). In addition, the possible release of chemicals is tested. For this purpose, compost samples are taken every two weeks and are tested for the pollutant groups PCB and PAH using gas chromatography. The results show that there is no noticeable decomposition after the said testing period. As for the release of pollutants, few PCBs are detected in the compost. It can be assumed that this is a background contamination, no pollutants seem to be released from the test material.